PENINGKATAN PEMAHAMAN KONSEP PELURUHAN ALFA MELALUI PEMBELAJARAN DENGAN SIMULASI PHET PADA SISWA MAN INDRAPURI - Zulkarnaini Zulkarnaini; Bukhari Bukhari; Ofi Ardianti (Jurnal Dedikasi Pendidikan, 2020)
The use of phet simulation media is not only to replace the role of real laboratories, but also as a complementary solution to the incompleteness of real laboratory facilities and equipment in schools. This media is also certain to make students interesting and motivated so that completing student learning outcomes will ultimately increase understanding of concepts in physics material. This study aims to determine the extent of the use of Phet simulation media can improve student understanding of concepts compared to conventional methods. This research is a quantitative study, with the method being true experimental; while the design used is the randomized pretest-posttest control group design. As a population of students in class XII MAN Indrapuri, while the sample is class XII-I and XII-2 which are selected randomly and act as the experimental class and the control class. Furthermore, it is analyzed using the N-Gain index, normality test, homogeneity test and statistical test. It can be concluded that learning through Phet simulation is better than conventional learning, with an average increase in N-Gain students' concept understanding of the experimental class 78.4% and the control class 52.1%.